Demersal fIsh assemblages along the Pacific coast of Costa Rica: a quantitative and multivariate assessment based on the Victor Hensen Costa Rica Expedition (1993/1994) - Wolff, Matthias (1996)
During two cruise legs with the RV Victor Hensen (December 1993, February 1994), the demersal fish assemblages of the Golfo de Nicoya (GN). Bahia Coronado-Sierpe Terraba (ST) and Golfo Dulce (GD) areas were assessed from nearshore (-20 m) to shelf edge (-200 m) waters. 44 Beam- and 29 otter trawl collections were made on an area of 2 119 405 m2, yielding a total of 242 species of fish. Despite the lower number of samples taken, more species were collected by the otter trawl (189 compared to 160), due to a wider area swept. As revealed by the species-area curve and a lognormal - curve constricted from the pooled (log) abundance data, the fish assemblage appeared as well sampled and a theoretical species richness (SR) of - 306 was estimated for the whole area. Mean species number per collection and mean biomass per area were much lower in the GD - area (9.3 species. O.36g /m2) compared to the ST (15.4, 0.81g/m2) and GN (17.3.0.74 g/m2) areas. indicating a depauperate fish assemblage in the former. Lowest species numbers and biomass were found in the central deep pan of GO with increasing values towards the still area at the opening of the gulf and towards the shallow stations above the thermocline. Average biomass was an order of magnitude higher in the interior pan of GN compared 10 the other areas with values up 10 18.1 g/m2. Based on results of a multivariate analysis of the col1ections, the GN area can be divided into (I) an interior shallow area above the thermocline (<50 m) characterized by scianids, sea catfishes, stingrays, flatfishes, sea robins, (2) an outer patt (>100 m) characterized by cods, scorpionfishes, gobies, cutlassfishes, serranids, anglerfishes and flatfishes and (3) a transition zone of the central and lateral patts with a mixed species assemblage with carangids. pufferfish. snappers. several flatfish species and the lizardfish as common elements. Characteristic for the deep basin of GD were small species of the genera Cynoscion and Porichthys. These occurred in low densities. suggesting a reduced canying capacity of this deep basin for fish biomass in terms of food and oxygen. Species occurring at the shallow stations of GD are also found at a similar depth in the ocher areas. but many species are missing. namely ariids and many scianids found in the GN area. The species assemblage of the ST area resembles that of GN. Ariids. however. are missing here too. Biotic station parameters like species richness. biomass. abundance and production were not significantly correlated with abiotic parameters (temperature. oxygen. nutrients) suggesting that other habitat factors not evaluated in this study like habitat heterogeneity, distance to the open ocean. current regime and food availability probably are important factors for the structure of the fish assemblage.